THE INFLUENCE OF FACEBOOK SOCIAL MEDIA USE ON EMPLOYEE WORK BEHAVIOR AT WONOSARI CAMAT OFFICE - andrianus eko saputra eko; ikram muhammad; maman musa (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to analyze the of Is there any effect of using social media on the work behavior of employees at the Wonosari sub-district office. To answer this research question, an associative type of research is used with a quantitative approach with social media facebook as a variable (X) and employee work behavior as a variable (Y). premiere data collection was used through questionnaires which were distributed to 30 respondents with saturated sampling technique or all members of the population, namely the Wonosari sub-district office employees as sample members. The results of data collection were then analyzed using correlation and regression analysis techniques with the help of the SPSS version 17 application program. The results showed that there was no significant effect of social media on the work behavior of employees at the Wonosari sub-district office, with an influence contribution of 7.70% and the rest explained by regulatory factors. So that the expected merit system of employee management can actually be realized in the Regional Government of Boalemo Regency, especially Wonosari District in order to realize a professional government bureaucracy.